The Role of Hadith in Shaping Social Media Use Ethics Among Generation Z - Aulia, Silvi Nur Izzatul; Fathoniz Zakka (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2024)
This research examines the role of hadith in shaping the ethics of using social media among Generation Z. Gen Z, who grew up in the digital era, is very familiar with technology and social media, but often lacks strong ethical guidelines in using these platforms. In this context, hadith as a source of Islamic moral teachings provide important guidance regarding ethical behavior, including interactions on social media. Hadiths such as authentic Muslim history no. 64 teaches the importance of guarding one's words and deeds, which is relevant to today's digital ethics. This research uses qualitative methods with a descriptive-analytical approach to understand the challenges of digital ethics among Gen Z and how hadith can provide relevant guidance in facing these challenges. The research results show that hadith teachings can be applied in a modern context as a guide for the younger generation to use social media wisely, responsibly and ethically. Hadith not only teaches to avoid negative behavior such as slander and hate speech, but also encourages the spread of goodness in cyberspace. By applying hadith values, it is hoped that Gen Z can become more responsible social media users and contribute positively to society.